Endovascular repair with covered stent for a giant hepatic artery pseudoaneurysm: a case report and literature review - Hou, Qingchun; Wei, Wei; Wang, Weiming; Mao, Weijian; Xu, Yanneng; Hu, Wei; Si, Guangyan; Yuan, Gang (Frontiers in Medicine, 2025)
Hepatic artery pseudoaneurysm (HAP), a rare life-threatening complication, typically occurs following trauma or surgical procedures such as liver transplantation. Initially asymptomatic, its rupture risk escalates with increasing size. Once ruptured, it carries an extremely high mortality rate, and delayed intervention may lead to fatal hemorrhagic shock. Consequently, early diagnosis and timely intervention are pivotal in managing HAP. Herein, we present a case of a HAP measuring approximately 10 cm in diameter. The patient was admitted with abdominal pain, and the clinical history did not indicate a definitive etiology. Computed tomography angiography revealed that the rupture site of the pseudoaneurysm was located in the common hepatic artery, with partial thrombus formation within the aneurysmal sac. The expansive lesion compressed the hepatic artery, resulting in hypoperfusion. Following multidisciplinary consultation and obtaining informed consent from the patient and her family, the patient underwent endovascular treatment under local anesthesia. During the procedure, two covered stents were successfully implanted. Postoperatively, the rupture of the HAP was effectively excluded, hepatic arterial patency was restored, and the patient’s abdominal pain was alleviated significantly. She was discharged 5 days after receiving antiplatelet and anti-infective therapy. Long-term antiplatelet treatment was continued, and at a one-year follow-up, the stent remained patent with no evidence of lesion recurrence. This case report, combined with literature review, aims to analyze HAP etiology and summarize diagnostic and therapeutic experiences.